2011
DOI: 10.5539/ass.v7n2p107
|View full text |Cite
|
Sign up to set email alerts
|

Performance Determinants of Kenya Certificate of Secondary Education (KCSE) in Mathematics of Secondary Schools in Nyamaiya Division, Kenya

Abstract: The study found the performance determinants of students’ performance in mathematics Kenya certificate of secondary education (KCSE) in Nyamaiya division of Kenya. The study employed descriptive survey design of the ex-post facto type with a total student population of 151 and 12 teachers. Four validated research instrument developed for the study were Mathematics Achievement Test (MAT) (r = 0.67), Students Questionnaire (SQ) (r = 0.75), Teachers Questionnaire (TQ) (r = 0.60 and Head teachers Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 7 publications
(6 reference statements)
4
36
0
Order By: Relevance
“…The findings of this study concur with the findings of Adeyemi (2010), and Yala and Wanjohi (2011), that teachers' teaching experience and academic qualifications were most important predictors of students' academic achievement.…”
Section: Discussion Of the Findingssupporting
confidence: 81%
“…The findings of this study concur with the findings of Adeyemi (2010), and Yala and Wanjohi (2011), that teachers' teaching experience and academic qualifications were most important predictors of students' academic achievement.…”
Section: Discussion Of the Findingssupporting
confidence: 81%
“…Studies in Mathematics education have examine the relationship between students' academic performance and their teacher's academic qualification, and in most case the teachers academic qualification and students' performance are positively correlated [27]. The study by [4,22,30] also had slightly similar results of positive correlation between student academic performance and teachers' qualification although extremely greater percentage of the student had viewed teacher's qualification to have negatively correlated with the student academic performance.…”
Section: Teachers' Self-efficacy and Certificationmentioning
confidence: 93%
“…Though limited studies have investigated this link, we posit that the unique nature of the Kenyan education system might have a role to play in this association, which appears to be potentially pathological. Studies have shown that the Kenyan adolescents face increased psychosocial pressure to succeed academically--due to familial sacrifices to pay school fees and the "do or die" mentality associated with exam success (upon which future education and career opportunities are hinged)--which exacerbate depression symptoms Yara & Wanjohi, 2011). As a result, we suggest that the association between trouble concentrating and selfblame in depression amongst Kenyan adolescents might help us understand academic functioning and achievement in this population and future studies should explore this possibility.…”
Section: Adolescent Depression Symptom Networkmentioning
confidence: 99%